MANAJEMEN KRISIS: KOMUNIKASI KRISIS DALAM PUBLIC RELATIONS PADA BANK INDONESIA - Ivan Godang Wardiman; Siti Amanah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The Coronavirus is a global pandemic that occurs in almost all countries in the world. This pandemic indirectly attacked the economies of each affected country and caused a crisis. This study discusses to explore and analyze the communication of public relation at one of the government institutions, Bank Indonesia. This study uses a qualitative approach using descriptive analysis. The type of data used is secondary data based on literature studies. The results of this study that Bank Indonesia already has a public relations division that handles crises and carries out communication strategies and media relations. The conclusion is that Bank Indonesia conducts crisis management quite well because it follows the stages and protocols in overcoming the crisis that occurred.